PolyICLC Exerts Pro- and Anti-HIV Effects on the DC-T Cell Milieu In Vitro and In Vivo. - Meropi Aravantinou; Ines Frank; Magnus Hallor; Rachel Singer; Hugo Tharinger; Jessica Kenney; Agegnehu Gettie; Brooke Grasperge; James Blanchard; Andres Salazar; Michael Piatak; Jeffrey D Lifson; et al. (PLoS ONE)
Myeloid dendritic cells (mDCs) contribute to both HIV pathogenesis and elicitation of antiviral immunity. Understanding how mDC responses to stimuli shape HIV infection outcomes will inform HIV prevention and treatment strategies. The long double-stranded RNA (dsRNA) viral mimic, polyinosinic polycytidylic acid (polyIC, PIC) potently stimulates DCs to focus Th1 responses, triggers direct antiviral activity in vitro, and boosts anti-HIV responses in vivo. Stabilized polyICLC (PICLC) is being developed for vaccine adjuvant applications in humans, making it critical to understand how mDC sensing of PICLC influences HIV infection. Using the monocyte-derived DC (moDC) model, we sought to describe how PICLC (vs. other dsRNAs) impacts HIV infection within DCs and DC-T cell mixtures. We extended this work to in vivo macaque rectal transmission studies by administering PICLC with or before rectal SIVmac239 (SIVwt) or SIVmac239ΔNef (SIVΔNef) challenge. Like PIC, PICLC activated DCs and T cells, increased expression of α4β7 and CD169, and induced type I IFN responses in vitro. The type of dsRNA and timing of dsRNA exposure differentially impacted in vitro DC-driven HIV infection. Rectal PICLC treatment similarly induced DC and T cell activation and pro- and anti-HIV factors locally and systemically. Importantly, this did not enhance SIV transmission in vivo. Instead, SIV acquisition was marginally reduced after a single high dose challenge. Interestingly, in the PICLC-treated, SIVΔNef-infected animals, SIVΔNef viremia was higher, in line with the importance of DC and T cell activation in SIVΔNef replication. In the right combination anti-HIV strategy, PICLC has the potential to limit HIV infection and boost HIV immunity.